Formation of Future Primary School Teachers’ Readiness for Conducting Pedagogical Diagnostics Based on ICT - Ziyabekova, Bota; Zhumabaeva , Aziya (Pedagogy and Psychology, 2025)
The study addresses the issue of preparing future primary education teachers for conducting pedagogical diagnostics based on information and communication technologies, identifying the main possibilities of ICT-based preparation in universities for effective diagnostic practices in primary education settings. Methodology and Methods. The research employed analysis of scientific literature to examine the current state of preparing future primary education teachers for conducting pedagogical diagnostics using information and communication technologies. A survey was conducted among teachers working in primary grades at secondary school № 185 in Almaty to determine their opinions and views on the possibilities of using information technologies for conducting pedagogical diagnostics. Results. Based on the literature study, the current state analysis revealed the relevance of ICT-based pedagogical diagnostics preparation for future primary education teachers. The survey results demonstrated specific opportunities that need to be provided when preparing future primary school teachers for pedagogical diagnostics based on information and communication technologies. Teachers’ opinions and views provided insights into practical requirements and possibilities for implementing ICT-based diagnostic approaches in primary education. Scientific novelty. The research contributes to understanding the specific requirements and possibilities for preparing future primary education teachers in ICT-based pedagogical diagnostics, establishing the theoretical foundation for integrating information technologies into diagnostic preparation programs and identifying key areas for improvement in teacher education. Practical significance. The findings provide evidence-based recommendations for universities preparing future primary education teachers, offering insights into necessary opportunities and approaches for effective ICT-based pedagogical diagnostics training that can enhance the quality of diagnostic practices in primary education settings.